Innovation in the market of financial services of the digital economy: general trends and prospects - Нікіфоров, Петро; Бабух, Ілона; Поченчук, Галина (Black Sea Research Institute of Economics and Innovation, 2021)
The rapid development of the digital economy and digital society through the use of new technologies has a significant impact on the financial sector, the institutions of which mediate almost all transactions of economic entities. Financial innovations are becoming an important factor in changes in financial markets. The latter appear in the financial services market under the influence of demand and supply factors, the former expand affordability and inclusiveness, while the others combine financial products, services within the financial ecosystem or marketplace. Technologies that change the Fintech industry are grouped into several separate groups, the application of these technologies changes the institutional environment, and the latter singles out financial regulators that use regulatory and supervisory technologies. The global Fintech market has significant potential and a number of new opportunities in the future. In Ukraine, the Fintech industry is actively developing, while the main problems of the domestic Fintech market are insufficient funding, a narrow area of specialization, insufficient level of cooperation with banks.
Інновації на ринку фінансових послуг цифрової економіки: загальні тенденції та перспективи
Keywords: digital economy; financial innovations; financial market; financial marketing; cognitive technologies; distributed computing; technologies in the field of cybersecurity; disruptive innovations; digital format; digital format; financial technologies; FinTech companies